Dermal fibroblast extracellular matrix regulates keratinocyte behaviour - Wong, Chee Wai (Curtin University, 2017)
This project explored using dermal fibroblast-derived extracellular matrices (ECMs) to recapitulate the keratinocyte microenvironmental niche in vitro. The data indicated that fibroblast-derived matrices better supported keratinocytes expansion than substrates of type I collagen. ECM composition was found to profoundly alter the gene expression profiles of keratinocytes grown on these matrices, in that foetal matrices triggered expression of cell cycle genes, whereas adult matrices triggered the expression of a balance of differentiation and cell cycle genes.